When dyspnoea mimics depression: a consultation-liaison psychiatry algorithm for distress and decisional capacity in ventilatory pump failure - De Queiroz, Felipe; Jordão, Natalia; Kaur, Maninderpal; Bach, John (Medycyna Paliatywna/Palliative Medicine, 2026)
Ventilatory pump failure (VPF) due to neuromuscular disease or high cervical spinal cord injury commonly precipitates hospital crises involving noninvasive ventilation, tracheostomy ventilation, or withdrawal of ventilatory support. Consultation-liaison (C-L) psychiatrists are often asked to assess depression, decisional capacity, and the meaning of requests to forgo lifesustaining treatment. A recurrent pitfall in such assessments is clinical pessimism, i.e. clinicians’ systematic underestimation of quality of life (QoL) in severe disability, a phenomenon related to the disability paradox. This review aimed to synthesize evidence on QoL and psychological adaptation in VPF and to propose a clinically actionable C-L psychiatry framework for assessment, differential diagnosis, interdisciplinary management, and documentation in high-stakes ventilation decisions. We conducted a narrative review of peer-reviewed studies, clinical guidelines, and bioethical literature relevant to ventilator-assisted living, disability adaptation, dyspnoea and anxiety, demoralization, and decisional capacity. PubMed/MEDLINE was searched from 1990 to October 2025 using combinations of VPF and neuromuscular ventilation terms with QoL and life satisfaction, disability paradox, response shift, affective forecasting, dyspnoea, demoralisation, and capacity terms. Reference chaining was used to supplement retrieval. Across cohorts of longterm ventilator users, many patients report satisfactory or good QoL despite profound functional dependence. Foundational work showed that ventilator-assisted individuals rated life satisfaction at approximately 5.1/7, whereas healthcare professionals estimated it at 2.42/7, indicating marked clinician pessimism. Contemporary studies likewise report that many ventilator-dependent patients rate QoL as good or excellent. Modifiable correlates include access to communication, participation outside the home, stable caregiving, and time since ventilation initiation. In VPF, C-L psychiatrists can support preference-concordant decisions by prioritising physiological and communication stability, distinguishing major depressive disorder from demoralisation and dyspnoea-related anxiety, facilitating interdisciplinary alignment, and documenting decisions in a way that minimises bias and symptom coercion.